IDEOLOGICAL AND POLITICAL EDUCATION MANAGEMENT MODEL FOR ART DESIGN MAJORS IN COLLEGES AND UNIVERSITIES UNDER LIAONING PROVINCE - Zi, Zhuang; Chinatangkul, Chuanchom; Chaisirithanya, Kamolmal (วารสารวิจัยธรรมศึกษา, 2025)
The objectives of this research were: (1)to determine the components and indicators of ideological and political education management for art design majors in colleges and universities under Liaoning Province;(2)to propose the ideological and political education management model of art design majors in colleges and universities under Liaoning Province;and(3)to develop implementation guidelines for ideological and political education management of art design majors in colleges and universities under Liaoning Province. The research was a mixed methodology research, including qualitative research and quantitative research. The population were 911 art design teachers and ideological and political education administrators in 14 colleges and universities in Liaoning Province. The sample size was determined by the Krejcie and Morgan table (1970), it was 278. The sample was obtained by stratified random sampling. The tools used for data collection were semi-structured interviews form and five-level rating scale questionnaire as well as focus group discussions form. Descriptive statistics content analysis and confirmatory factor analysis were used for data analysis.The research findings revealed that: (1) The components and indicators of ideological and political education management of art design majors in colleges and universities under Liaoning province consisted of seven components and 62 indicators; (2) The ideological and political education management model of art design major in colleges and universities in Liaoning province was fit with the empirical data model; and (3) The implementation guidelines for ideological and political education management of art design majors in colleges and universities under Liaoning Province were 26 guidelines.